Going unscripted: A call to critically engage storytelling methods and methodologies in geography and the medical‐health sciences. (18th January 2017) - de Leeuw, Sarah; Parkes, Margot W.; Morgan, Vanessa Sloan; Christensen, Julia; Lindsay, Nicole; Mitchell‐Foster, Kendra; Russell Jozkow, Julia
Abstract : Geography and the medical‐health sciences have long histories of engaging the humanities. The last decade has seen for both disciplines a significant growth in theoretical frameworks, pedagogic strategies, and research methods that draw upon visual and literary arts, critical self‐reflection, creative tools and expressions, and even direct engagement or partnership with artists, curators, authors, theatre‐practitioners, and other professionals in the arts. Both geographers and medical‐health professionals, then, are increasingly (re)making and understanding various worlds through the humanities. In this paper we explore the histories of humanities in both geography and the medical‐health sciences, especially medicine: we argue the two disciplines have much to learn from each other's engagement and work with the humanities. Focusing on the increasing use of narrative and storytelling in both disciplines, we argue that deployment of humanities‐based frameworks and impulses must not be taken up without careful and critical analytical reflection. Finally, we ground our theoretical explorations with empirical examples from recent community‐based work about the risks and benefits of storytelling and visual arts when looking at the health geographies of Indigenous and settler peoples in Northern British Columbia. De manière impromptue : vers une démarche critique sur les méthodes de mise en récit et les méthodologies en géographie et en sciences médicales et de la santé: L'intérêt pour les sciences humaines par la géographie et les sciences médicales et de la santé s'inscrit dans une longue tradition. Au cours de la dernière décennie, les deux disciplines ont connu une importante croissance de cadres théoriques, de stratégies pédagogiques et de méthodes de recherche qui font appel aux arts visuels et à la littérature, à l'autoréflexion critique, à des outils et modes d'expression novateurs, voire même à une participation directe ou à des partenariats avec des artistes, conservateurs, auteurs, praticiens de l'art dramatique et d'autres professionnels du domaine des arts. Autant les géographes que les professionnels de la médecine et de la santé contribuent de plus en plus à (re)constituer et comprendre divers mondes à travers les sciences humaines. Cet article brosse un tableau historique des sciences humaines tant en géographie qu'en sciences médicales et de la santé, en particulier la médecine : nous soutenons que les deux disciplines ont beaucoup à apprendre l'une de l'autre sur l'intérêt que chacune porte aux sciences humaines. En mettant l'accent sur le recours grandissant par les deux disciplines à la narration et à la mise en récit, nous faisons valoir l'idée que le déploiement des cadres et des impulsions fondés sur les sciences humaines ne peut pas être envisagé sans mener au préalable une réflexion analytique minutieuse et critique. Enfin, nous fondons cette étude du champ théorique sur des exemples empiriques tirés de travaux réalisés à l'échelle communautaire sur les risques et les avantages de la mise en récit et des arts visuels quand on se penche sur les aspects géographiques de la santé des peuples autochtones et colonisateurs dans le nord de la Colombie‐Britannique. Key Messages: Although stories and storytelling have long and varied histories across multiple geographies, they are increasingly being valorized in new and public ways. Drawing from feminist, Marxist, anti‐racist, and decolonizing theoretical frameworks, we critically unpack humanities‐based happenings and (re)read the "creative re‐turn" in geography and medical‐health sciences. We conclude with reflections about anti‐hegemonic ways humanities‐informed methods and methodologies, including stories and storytelling, might be taken up in an "unscripted" way by geographers and medical‐health researchers.